Media Coverage of Sexual Violence Cases in the Russia-Ukraine War - Hadidah Sallimi; Sidik Jatmika (Prodi Hubungan Internasional Program Magister Univ. Muhammadiyah Yogyakarta, 2024)
The purpose of this research is to examine how international news sources have narrated the sexual violence issues during the recent Russia-Ukrainian conflict. This research used the Narrative Policy Framework to analyze not only the function of news narratives but also the elements (such as characters) portrayed in rape cases (criminals, heroes, and victims). Furthermore, NVivo Pro was used to process the research data qualitatively. According to the findings, international news sources like The Guardian, CNN, and Al Jazeera have largely reported on the claim that sexual violence, especially rape, has been used as a 'weapon' by the Russian military in its attacks on Ukraine. Ukrainian women, men, children, girls, and boys make up the vast majority of the victims here. Meanwhile, the Russian government and army are presented as villains in the narrative. Different narratives emerge when the three media outlets discuss actors in terms of heroic roles, as shown by this research. There are signs that the media has its objectives, particularly in the context of the Ukraine-Russia war, based on the disparities between the narratives given to the hero characters by the media.